Financial performance and market value sector telephony in Brazil - Resende Silva, Carolina Terra [UNESP]; Lopes Santos, David Ferreira [UNESP] (Russian Soc Historians & Archivists, 2015)
This study investigated the relationship between traditional metrics of financial performance and the impact on the market value of the telephony companies in the Brazil, with stock in BM&FBOVESPA between 2002 and 2012. Constructed a database containing financial statements of the four companies with complete information for the period (TIM, Vivo, Embratel and Oi), which is based analyzed by regression using panel data method. The results indicate that traditional indicators of financial performance ROS, ROI, ROE, EBITDA margin were not able to explain the variation in market value, either, the metrics of value added EVA, MVA and RROI. In explaining the market value of these companies the Investment and WACC (Weighted Capital Average Cost) were found as significant.
Keywords: Market Value; Financial Performance; Sector Telephony